Review of global use of licensed vaccines and development of new vaccines for the prevention of pneumococcal infection - M. V. Savkina; M. A. Krivykh; N. A. Gavrilova; L. V. Sayapina; Yu. I. Obukhov; V. A. Merkulov; V. P. Bondarev (Биопрепараты: Профилактика, диагностика, лечение)
Streptococcus pneumoniae infection is the most common cause of high morbidity and mortality among children under 5 years of age, immunocompromised people, and the elderly. Despite significant success, the approved pneumococcal conjugate and polysaccharide vaccines are of limited efficacy, providing protection against a small fraction of the known pneumococcal serotypes. The rapid spread of multidrug-resistant strains exacerbates the global challenge of treating infection caused by S. pneumoniae. At the same time, the emerging new strains dictate the need to include new serotypes into vaccines. In view of this, further improvement of vaccines for the prevention of pneumococcal infections is an urgent task. The aim of this study was to review advances in the development of polysaccharide, conjugate, whole-cell pneumococcal vaccines, as well as vaccines based on protein antigens and vaccines with an antigen delivery system. Genomics and proteomics data have helped to improve approaches to the creation of polysaccharide and protein-based vaccines, as well as whole-cell vaccines with the potential for population prophylactic coverage against various pneumococcal serotypes that are not included in the licensed pneumococcal vaccines. The method of antigen delivery to the cell is of great importance in the development of vaccines. The most promising strategy for improving pneumococcal vaccines is the creation of vaccines based on bacterium-like or synthetic particles carrying several antigens, including pneumococcal surface proteins. In conclusion, it should be noted that top-priority vaccines are those that provide a wide range of protection against circulating pneumococcal serotypes and, in addition to eliciting a systemic immune response, also induce local immunity.